PEMANFAATAN MINYAK JELANTAH SEBAGAI LILIN AROMATERAPI - Rosmita Nuzuliana,; Devi Latifatul Fitri,; Elsafira silvia,; Rima Anggraini,; Seylla Praba Surya Apriliana Wati, (Jurnal Cakrawala Ilmiah, 2023)
: In everyday life, people cannot be separated from the use of cooking oil and this cooking oil is also not only used for one use or what is often called used cooking oil. This used cooking oil has a very bad impact on the health of the body and the surrounding environment. Therefore, we need to minimize used cooking oil through recycling and reducing or what is usually called reusing used cooking waste and reducing used cooking waste. One way to reduce used cooking oil waste is by processing used cooking oil as aromatherapy candles. The aim of this service activity is to increase community knowledge in managing waste from used cooking oil which can apparently be used as aromatherapy candles. The method used is by providing material regarding used cooking oil, then how to make used cooking oil into aromatherapy candles. The results obtained after providing the materials and practice of making candles, there was an increase in public knowledge about the bad effects of used cooking oil, as well as increasing the community's skills in using used cooking oil to make aromatherapy candles.